Syphilis in pregnancy and congenital syphilis in Amazonas State, Brazil: an evaluation using database linkage - Claudia Marques de Oliveira Soeiro; Angélica Espinosa Miranda; Valeria Saraceni; Marcelo Cordeiro dos Santos; Sinesio Talhari; Luiz Carlos de Lima Ferreira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
This study analyzes notification of syphilis in pregnancy and congenital syphilis in Amazo- nas State, Brazil, from 2007 to 2009 and verifies underreporting in databases in the National Information System on Diseases of Notification (SINAN) and the occurrence of perinatal deaths associated with congenital syphilis and not reported in the Mortality Information System (SIM). This was a cross-sectional study with probabilistic record linkage between the SINAN and SIM. There were 666 reports of syphilis in pregnant women, including 224 in 2007 (3.8/1,000), 244(4.5/1,000) in 2008, and 198(4.0/1,000) in 2009. The study found 486 cases of congenital syphilis, of which 153 in 2007 (2.1/1,000), 193 in 2008 (2.6/1,000), and 140 in 2009 (2.0/1,000). After linkage of the SINAN databases, 237 pregnant women (35.6%) had cases of congenital syphilis reported. The SIM recorded 4,905 perinatal deaths, of which 57.8% were stillbirths. Probabilistic record linkage between SIM and SINAN-Congenital Syphilis yielded 13 matched records. The use of SINAN and SIM may not reflect the total magnitude of syphilis, but provide the basis for monitoring and analyzing this health problem, with a view towards planning and management.